Chapter 19 Toxic speech, political self-Indigenization and the ethics and politics of critique Notes from Finland - Junka-Aikio, Laura (Taylor & Francis, 2022)
Over the past decades, online hate speech against the Indigenous Sámi people has sharply proliferated, and in each Nordic country, it is now considered a problem requiring counter-measures and further study. This chapter employs Lynne Tirrell's notion of toxic speech to examine anti-Sámi hate speech that is specific to the political terrain in Finland. There, such speech is particularly common in debates which centre on criticism of the Sámi Parliament, voiced mainly by popular movements which promote political self-Indigenization to gain access in the Sámi Parliament's electoral register. Although these movements make explicit use of academic knowledge production and discourses which highlight Sámi cultural revitalization and recovery, the study shows how, on the level of popular rhetoric and in the social media, the same discourses are operationalized to purposefully undermine Sámi peoplehood and rights, to denigrate any individual or institution which is seen to defend such rights, and to disseminate pejorative representations of the Sámi. The chapter ends with a short exploration of possible reasons which explain why this form of toxic speech has so far been particularly impervious to criticism and public exposure.